2013
DOI: 10.1089/scd.2012.0708
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory microRNA Network Identification in Bovine Blastocyst Development

Abstract: Mammalian blastocyst formation is characterized by two lineage segregations resulting in the formation of the trophectoderm, the hypoblast, and the epiblast cell lineages. Cell fate determination during these early lineage segregations is associated with changes in the expression of specific transcription factors. In addition to the transcription factor-based control, it has become clear that also microRNAs (miRNAs) play an important role in the post-transcriptional regulation of pluripotency and differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 58 publications
2
30
0
1
Order By: Relevance
“…Furthermore, microRNA levels undergo dynamic changes during preimplantation development of murine embryos (Mineno et al, 2006;Yang et al, 2008;Viswanathan et al, 2009): for example, total microRNA in four-cell stage embryos is double that at the two-cell stage (Tang et al, 2007). In bovine embryos, Goossens et al (2013) showed that microRNAs regulate the balance between pluripotency and differentiation into trophectoderm and inner cell mass. Besides their known function in gene regulation, secreted microRNAs have recently received increasing attention for their role in intercellular communication and the manner in which secreted microRNAs from donor cells influence gene expression of recipient cells (Valadi et al, 2007).…”
Section: (3) Micrornasmentioning
confidence: 99%
“…Furthermore, microRNA levels undergo dynamic changes during preimplantation development of murine embryos (Mineno et al, 2006;Yang et al, 2008;Viswanathan et al, 2009): for example, total microRNA in four-cell stage embryos is double that at the two-cell stage (Tang et al, 2007). In bovine embryos, Goossens et al (2013) showed that microRNAs regulate the balance between pluripotency and differentiation into trophectoderm and inner cell mass. Besides their known function in gene regulation, secreted microRNAs have recently received increasing attention for their role in intercellular communication and the manner in which secreted microRNAs from donor cells influence gene expression of recipient cells (Valadi et al, 2007).…”
Section: (3) Micrornasmentioning
confidence: 99%
“…However, its expression during early development remained undefined. A first analysis of miR-203 levels during normal murine and bovine preimplantation development suggested a modest but specific wave of expression during the 2-cell stage and early blastocysts, whereas its expression was lost in cultured embryonic stem cells 11,12 . Quantitative PCR analysis in mouse embryos isolated at different developmental stages showed that miR-203 expression was low in oocytes, slightly induced at the 2-cell stage and displayed a gradual reduction in morulas and blastocysts ( Fig 1A).…”
Section: Mir-203 Improves the Differentiation Potency Of Pscsmentioning
confidence: 99%
“…All the chimeric experiments were reviewed and approved by the Salk Institutional Animal Care and Use Committee (IACUC) and followed the ethical guidelines of the Salk Institute. For RNA interference assays, ON-TARGETplus SMARTpool for Non-targeting control siRNA (D-001810-01, 02, 03, 04), Dnmt3a siRNAs (J-065433-09, 10,11,12) and Dnmt3b siRNAs (J-044164-05, 06, 07, 08) from Dharmacon were used.…”
Section: Interspecies Chimeric Assaysmentioning
confidence: 99%
“…Metabolomics and proteomics profiling technologies may allow determination of the metabolites associated with embryo viability and thereby predicting pregnancy outcome (Gardner et al, 2001;Sturmey et al, 2010). Metabolomics, the newest emerging technology, includes analysis of spent culture media for the small non-coding RNA, including microRNA (Rødgård et al, 2015), demonstrated to be important to embryogenesis and development (Goossens et al, 2013). Therefore, new screening tools based on embryo quality and viability assessment could have a huge impact on prediction of pregnancy rates and the efficiency of ET programs with IVP embryos.…”
Section: In Vitro Produced Embryosmentioning
confidence: 99%